2008
DOI: 10.1590/s0100-879x2008000800005
|View full text |Cite
|
Sign up to set email alerts
|

Vascular complications of black patients with type 2 diabetes mellitus in Southern Brazil

Abstract: Ethnicity has been shown to be associated with micro-and macrovascular complications of diabetes in European and North American populations. We analyzed the contribution of ethnicity to the prevalence of micro-and macrovascular complications in Brazilian subjects with type 2 diabetes attending the national public health system. Data from 1810 subjects with type 2 diabetes (1512 whites and 298 blacks) were analyzed cross-sectionally. The rates of ischemic heart disease, peripheral vascular disease, stroke, dist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 28 publications
1
6
0
Order By: Relevance
“…In Saudi Arabia, women had significantly higher rates of diabetic retinopathy than men, which is in agreement with a study in Sweden where women had higher rates than men49 and in other studies 13,19. Two further studies have suggested nonsignificant differences in diabetic retinopathy according to gender 50,51.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…In Saudi Arabia, women had significantly higher rates of diabetic retinopathy than men, which is in agreement with a study in Sweden where women had higher rates than men49 and in other studies 13,19. Two further studies have suggested nonsignificant differences in diabetic retinopathy according to gender 50,51.…”
Section: Discussionsupporting
confidence: 90%
“…However, their analysis revealed that diabetic retinopathy in the study sample was only marginally associated with hypertension, which is widely regarded as a significant risk factor for diabetic retinopathy in most studies 10,19. Improved monitoring and control of hypertension among diabetic patients in the United Arab Emirates, which has been shown to slow the progression of retinopathy, particularly among those with poorly controlled diabetes, is strongly recommended 20…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Brazil had the most scientific production with fourteen studies [ 53 , 55 58 , 60 , 61 , 64 66 , 71 , 72 ], Mexico with seven [ 52 , 54 , 67 , 68 , 70 , 73 , 74 ], Peru with four [ 59 , 69 , 74 , 77 ], and Cuba [ 51 ], Uruguay [ 63 ], and Ecuador with one study [ 62 ] ( Fig 2 ) . Regarding DM type, 22 studies included type 2 DM [ 52 57 , 59 62 , 66 , 68 78 ], three type 1 DM [ 58 , 65 , 67 ] and three in both types of DM [ 51 , 63 , 64 ], presenting combined prevalence. In twenty-one studies, patients were recruited from reference hospitals [ 51 , 54 59 , 61 , 63 – 67 , 69 , 70 , 72 74 ], four from primary care [ 52 , 53 , 60 ,…”
Section: Resultsmentioning
confidence: 99%
“…In twenty-one studies, patients were recruited from reference hospitals [ 51 , 54 59 , 61 , 63 – 67 , 69 , 70 , 72 74 ], four from primary care [ 52 , 53 , 60 , 68 ], and three from the general population [ 62 , 71 , 75 ]. According to the onset of DM, one study was made with newly detected DM (debut) [ 61 ], nine with DM patients with more than 5 years of illness [ 51 , 56 , 65 , 68 70 , 72 , 77 , 78 ], six with more than 10 years of disease [ 53 , 57 , 64 , 66 , 73 , 74 ], and eleven did not specify any time [ 52 , 54 , 55 , 58 60 , 62 , 63 , 71 , 75 , 76 ].…”
Section: Resultsmentioning
confidence: 99%